Research on the Application of Virtual Reality Technology in the Cultural Exchange of Tourist Attractions Under the Background of Artificial Intelligence - Hou, Na (International journal of information systems and supply chain management, 2024)
Virtual reality is an immersive interactive technology that captures the entire location within 360 degrees with the help of special cameras, mounts and software. This paper discusses the role of artificial intelligence technology and virtual reality technology in the cultural communication of tourist attractions. In tourist attractions, VR technology provides a glimpse of information about the tourist attraction with the help of VR photography and VR video. This study provides a new idea for the design of interactive cultural communication devices and uses supervised learning algorithms to make their versatility and interactivity fully reflected in the communication effect . The results of the study show that by using supervised learning algorithms, artificial intelligence based virtual reality provides 97% high accuracy.